2019
DOI: 10.1515/reveh-2018-0059
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modifications associated with in utero exposure to endocrine disrupting chemicals BPA, DDT and Pb

Abstract: Endocrine disrupting chemicals (EDCs) are xenobiotics which adversely modify the hormone system. The endocrine system is most vulnerable to assaults by endocrine disruptors during the prenatal and early development window, and effects may persist into adulthood and across generations. The prenatal stage is a period of vulnerability to environmental chemicals because the epigenome is usually reprogrammed during this period. Bisphenol A (BPA), lead (Pb), and dichlorodiphenyltrichloroethane (DDT) were chosen for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 154 publications
0
27
0
Order By: Relevance
“…The specific manifestations are: disruption of major weight control hormones such as catecholamine, thyroid hormone, estrogen, insulin, growth hormone, leptin, testosterone and corticosteroids; altered hormone sensitivity, especially for dopamine, serotonin, and angiotensin; and disruption of metabolic processes. Together, these effects can lead to tissue and organ damage, especially in nerves and muscles [12][13][14][15][16] , even at low levels of exposure. In our study, pregnant mice were administered DBP was from the 12th day of gestation to the 7th day after birth, a critical period in the differentiation of adipose tissue, reproductive organs and the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…The specific manifestations are: disruption of major weight control hormones such as catecholamine, thyroid hormone, estrogen, insulin, growth hormone, leptin, testosterone and corticosteroids; altered hormone sensitivity, especially for dopamine, serotonin, and angiotensin; and disruption of metabolic processes. Together, these effects can lead to tissue and organ damage, especially in nerves and muscles [12][13][14][15][16] , even at low levels of exposure. In our study, pregnant mice were administered DBP was from the 12th day of gestation to the 7th day after birth, a critical period in the differentiation of adipose tissue, reproductive organs and the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…We also discovered that the urine BPA metabolite level was significantly higher in Taiwanese children than in those of other countries [9,10]. BPA has become serious public health problem globally and been described the various epigenetic mechanisms, like DNA methylation, histone modifications and non-coding RNAs, then affecting gene expression [11][12][13]. Furthermore, we found that exposure to this harmful chemical affected DNA methylation, which influenced the prevalence of allergic disorders in children [14].…”
Section: Introductionmentioning
confidence: 74%
“…As discussed previously, the mammary gland goes through several developmental periods including prenatal, postnatal, and puberty. During this time, the mammary gland might be more sensitive to epigenetic modifications and disruptions [8,9].…”
Section: Epigenetic Modificationsmentioning
confidence: 99%